304 Does nact reduce the extent of surgery and perioperative morbidity in surgical cytoreduction of advanced epithelial ovarian cancer? A single institute experience at fmri, gurugram. (18th September 2019) - Joshi, R; Rekha Bora, R; Raina, D; Ravi, AK
Abstract : Objectives: To study the extent of surgery to achieve completeness of cytoreduction (CC) score 0 and perioperative morbidity in interval surgical cytoreduction in comparison to primary surgical cytoreduction of advanced epithelial ovarian cancer. Methods: It is an interim analysis of ongoing prospective comparative study of patients with stage III/IV ovarian, tubal and peritoneal cancers undergoing interval or primary surgical cytoreduction during the period 2015 to 2018. The extent of surgery to achieve CC score-0 was the primary endpoint and perioperative morbidity was the secondary endpoint. Indication for NACT was bulky upper abdomen disease based on clinical evaluation and imaging or PS >2. Results: Among 124 cases, 73 were in stage III/IV epithelial cancer; 46 of them had NACT and underwent interval surgical cytoreduction and 27 had primary surgical cytoreduction. The two groups did not differ significantly in median surgical peritoneal carcinomatosis index (PCI) (p 0.5755) or surgery duration (p 0.2301). In the interval group 78.3% and in the primary group, 81.5% were cytoreduced to CC score of 0. The types of procedures to achieve CC 0 were not statistically different between the two groups. A higher incidence of paraaortic lymph node dissection was observed in the primary group (p 0.0137). The perioperative morbidity in the interval group was not significantly different from the primary group. Conclusions: In our experience, NACT could not significantly reduce the surgical extent to achieve CC 0 or the perioperative morbidity in comparison to patients undergoing primary surgical cytoreduction.